Nők a pénzintézeti szféra vezetésében - Bihari, Zsuzsanna (Tér és Társadalom, 1993)
Since 1987 Hungary has been operating a two-level bank system. The formation of commercial banks has created a great need for experts in a formerly closed and highly respected, yet poorly remunerated profession. It is particular to Hungary, that due to the low incomes, men previously avoided this sector of business. The rise of prestige of this profession has contributed to the rise of prestige of people engaged in this profession as well. This is not an ordinary turn in the case of professions cultivated primarily by women. Therefore, my investigation explores how women have been able to convert the gains obtained from an urgent need on the labor market into other sorts of advantage. I have drawn information, above all, from my own survey that I completed in the first halt of 1992. The survey questioned the managers of savings and commercial banks in the countryside. Due to the small size of my sample (108 questionnaires), I only raise some general questions and form initial hypotheses. My results show that men have three times higher chance to get into the top managerial strata. As opposed to men, those women, who are nominated into higher positions, have usually climbed the hierarchy within this particular sector of business. As far as marital status is concerned, three times more women appear to be single than men among the managers. There are also less divorced among men than among women. One can draw the consequence that for women career conveys private uncertainties and disadvantage while men in top positions usually enjoy a stable family background. Women in the management usually do not have husbands in a highly paid profession; therefore, these families could not afford to hire domestic help. Moreover, in these families the division of household labour follows a conventional pattern. In contrast, men in the management of financial business are supported by their wives' larger shares in the household burdens. It is a promising experience that in the families of younger professionals a more just division of labour is in progress.